CROSSLINGUISTIC REPOSITORY OF POLITICAL METAPHORS: STRUCTURE AND METHODOLOGICAL ISSUES - Inna V. Skrynnikova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2019)
The article presents a critical review of numerous approaches to the analysis of metaphor in various scientific traditions. The focus is set on the interdisciplinary methods applied in the metaphor studies which resulted in corpora, databases of figurative language and analysis of repositories of metaphors in English, French, and German. The question of reliable methods and procedures of identification of metaphors in modern linguistics is discussed in the article. The author praises efficiency of a metaphor methodology that was verified in the University of California (Berkley, USA), and considers possibility of its application for studies on Russian political metaphors through their comparison with English. The metaphors of government are used for exemplification of explanatory potential of an integrative approach that unites the opportunities of combining bottom-up and top- down procedures of identifying and analyzing metaphors within a single repository. The paper presents a procedure of deep multi-level semantic analysis of metaphors and dwells on techniques of formalizing the conception of neural cascades as applied to the analysis of metaphors. The author uncovers the problems in constructing the cross-linguistic (English and Russian) repository of political discourse metaphors. The proposed approach enables to determine interrelated conceptual networks and present metaphors at different levels of specificity and complexity of a multimodal model of metaphorical cognition.